Nilai-nilai Islam Pelaksanaan Tradisi Aggalara’ pada Acara Pasunna’ di Kabupaten Jeneponto Sulawesi Selatan - Henri Henri; Parham Taufik; Tiara Nur'aini (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
Aggalara’ tradition in the pasunna’ ceremony in Jeneponto Regency, South Sulawesi, is part of a cultural heritage that holds religious values, especially those related to Islam such as gratitude, brotherhood, trust, and education. This research aims to understand how these values are realized in the implementation of the tradition. The approach used is descriptive qualitative research with an ethnographic method, through direct observation, in-depth interviews, and documentation studies. Data is analyzed using Talcott Parsons' structural functionalism theory to reveal how this tradition functions in strengthening social bonds and maintaining balance in the community. The research results show that gratitude is reflected in expressions of thanks to God for the blessings of life and the successful conduct of the pasunna’ ceremony. Solidarity and family relationships within the community demonstrate a strong value of brotherhood. Value of trust can be seen from the responsibilities of traditional leaders in carrying out their roles, while education is evident in the process of passing values to the younger generation. Aggalara’ tradition not only preserves local cultural identity but also deepens Islamic values in a contextual manner. This finding emphasizes that local culture can be an effective instrument for educating religious values in everyday community life.